IMPLEMENTASI NORMA KESUSILAAN DAN KEADILAN TERHADAP TINDAKAN BULLYING - Sahrudin; Raden Bagus Mochammad Ramadhan Razief Hafid; Reva Hazarina; Nurkholis Anwar; Muhammad Haikal; UTM, Sahrudin (PT. Media Akademik Publisher, 2024)
Artikel ini berjudul